2007
DOI: 10.1111/j.1471-1842.2007.00713.x
|View full text |Cite|
|
Sign up to set email alerts
|

The information‐seeking behaviour of doctors: a review of the evidence

Abstract: This paper provides a narrative review of the available literature from the past 10 years (1996)(1997)(1998)(1999)(2000)(2001)(2002)(2003)(2004)(2005)(2006) that focus on the information seeking behaviour of doctors. The review considers the literature in three sub-themes: Theme 1, the Information Needs of Doctors includes information need, frequency of doctors' questions and types of information needs; Theme 2, Information Seeking by Doctors embraces pattern of information resource use, time spent searching, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
262
1
16

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 293 publications
(294 citation statements)
references
References 44 publications
15
262
1
16
Order By: Relevance
“…The results support that EBM is a well-known concept and physicians generally have a positive attitude towards it [4,5]. Our study confirms that time constraints, lack of skills in searching and appraising the literature and limited access to EBM sources are considerable barriers to answering clinical drug questions [1,3,4,11]. A study among Danish hospital physicians found that most of them seemed to lack knowledge of the most basic aspects of evidence-based medicine, and this may represent another substantial barrier to implementing EBM into clinical practice [7].…”
Section: Motives For Applying For Problem-oriented Drug Informationsupporting
confidence: 74%
See 4 more Smart Citations
“…The results support that EBM is a well-known concept and physicians generally have a positive attitude towards it [4,5]. Our study confirms that time constraints, lack of skills in searching and appraising the literature and limited access to EBM sources are considerable barriers to answering clinical drug questions [1,3,4,11]. A study among Danish hospital physicians found that most of them seemed to lack knowledge of the most basic aspects of evidence-based medicine, and this may represent another substantial barrier to implementing EBM into clinical practice [7].…”
Section: Motives For Applying For Problem-oriented Drug Informationsupporting
confidence: 74%
“…A great many of the questions concern pharmacotherapy. About 60% of the answers are simple, such as the dose of a drug, and can easily be located by looking in textbooks or medication databases [1]. Other questions are more complex and a large portion remain unanswered although in many cases an answer exists in the literature that would have changed the physician's decision [2,3].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations